The Efficacy and Safety of Apatinib Plus Camrelizumab in Patients With Previously Treated Advanced Biliary Tract Cancer: A Prospective Clinical Study - Wang, Dongxu; Yang, Xu; Long, Junyu; Lin, Jianzhen; Mao, Jinzhu; Xie, Fucun; Wang, Yunchao; Wang, Yanyu; Xun, Ziyu; Bai, Yi; Yang, Xiaobo; Guan, Mei; et al. (Frontiers in Oncology, 2021)
Background PD-1/L1 inhibitor-based immunotherapy is currently under investigation in biliary tract cancer (BTC). Apatinib combined with camrelizumab has achieved promising results in various tumor types. The aim of this study was to assess the safety and efficacy of apatinib plus camrelizumab for advanced biliary tract cancer patients who have received previously treatments. Methods This prospective, non-randomized, open-label trial was conducted at Peking Union Medical College Hospital (PUMCH). All included patients received apatinib orally at 250 mg per a day and camrelizumab intravenously at 200 mg every three weeks until disease progression or intolerable toxicity occurred. Efficacy was evaluated based on the Response Evaluation Criteria in Solid Tumors RECIST Version 1.1 (RECIST 1.1). Adverse events (AEs) were assessed by the National Cancer Institute Common Terminology Criteria for Adverse Events (CTCAE version 4.0). Results A total of 22 patients were consecutively enrolled from 1st December, 2018 until 1st August, 2020. Among 21 patients for whom we could conduct efficacy evaluations, no patients achieved a complete response (CR), 4 patients (19%) achieved partial response (PR), and 11 patients had stable disease with a disease control rate of 71.4%. The median overall survival was 13.1 months (95% CI, 8.1-18.2), and the median progression-free survival was 4.4 months (95% CI, 2.4-6.3). All patients experienced treatment related AEs, and grade 3 or 4 AEs occurred in 14 (63.6%) of 22 patients. No treatment related deaths were observed. Conclusions This is the first report focusing on the efficacy and safety of camrelizumab plus apatinib in pretreated biliary tract cancer patients. The finding suggests this regimen has favorable therapeutic effects with relatively manageable toxicity. Further trials with a control arm are required to investigate. Clinical Trial Registration identifier NCT04642664.